NSTE - ACS : guidelines for the management of acute coronary syndromes in patients presenting without persistent st-segment elevation (Vreckové odporúčania ESC, 2015)
The leading symptom in suspected acute coronary syndromes (ACS) is chest pain. Based on the electrocardiogram (ECG), two groups of patients should be differentiated: Patients with acute chest pain and persistent (>20 min) ST-segment and patients with acute chest pain but no persistent ST-segment elevation.